Beneficial Noncancerous Mutations in Liver Disease. Issue 7 (July 2019) - Müller, Miryam; Forbes, Stuart J.; Bird, Thomas G.
Abstract : Chronic liver disease results in fibrosis and cancer. While injury is associated with mutational burden, a recent study (Zhu et al. Cell 2019;177:608–621) highlights that not all positively selected mutations in the liver are precancerous. Indeed, some may be beneficial to the ability of the liver to not only withstand injury, but also to regenerate.